Water Use Efficiency for Wheat under Water Stress Conditions of Central Iraq - Ali A. Fahad; Ayad A. H. Al-Maeiny (Journal of Madenat Alelem University College, 2010)
The objective of the present work was to estimate water requirements and water use efficiency for wheat under conditions of normal irrigation and water stress in different plant growth stages. Field experiment was carried out at Tuwaitha Experimental Station of Agricultural Research Centre, Ministry of Science and Technology. The field was divided to apply a factorial experiment in split plot design using randomized complete block design in three replicates. Seeds of four cultivars (Abu-Ghraib, Tamooz 3, Al-Rasheed, and Al-Iraq) were planted in the sub plots where six of the water treatments distributed in the main plots. They were normal irrigation (no stress), and stress at tillering, elongation, spike formation, flowering, and grain filling. Irrigation water was applied in the normal irrigation when 65-70% of the available water was depleted and one irrigation was omitted for the water stress treatments. Actual and reference evapotranspiration, pan evaporation, grain yield, crop coefficient, and water use efficiency were estimated. Amounts of irrigation water and actual evapotranspiration differed for the cultivars and water stress treatments. Mean irrigation requirement for the four cultivars based on irrigation scheduling was 295 mm, decreased by 14% under stress conditions. On the other hand, the actual evapotranspiration was 365 mm, decreased by 17% under stress conditions of the drought tolerant stages. Maximum water consumptive use was obtained for the control treatment (no stress) for the cultivar Tamooz 3 (406 mm) and the minimum was for Al-Rasheed (324 mm). Grain yield ranged between 4.40 and 6.20 for water stress treatments compared to 5.60 and 6.80 ton/ha for normal irrigation treatments with Al-Iraq gave the highest and it differed significantly from others. Field water use efficiency ranged between 1.58 and 2.40 kg/m3 and crop water use efficiency 1.33 and 1.92 kg/m3 Results indicated that the stages of spike formation and flowering are the most tolerant to water stress. On the other hand, the elongation and grains filling were critical stages with high reduction in yield under stress conditions.